2012
DOI: 10.1007/s10732-012-9200-z
|View full text |Cite
|
Sign up to set email alerts
|

A tabu search algorithm for the minmax regret minimum spanning tree problem with interval data

Abstract: This paper deals with the strongly NP-hard minmax regret version of the minimum spanning tree problem with interval costs. The best known exact algorithms solve the problem in reasonable time for rather small graphs. In this paper an algorithm based on the idea of tabu search is constructed. Some properties of the local minima are shown. Exhaustive computational tests for various classes of graphs are performed. The obtained results suggest that the proposed tabu search algorithm quickly outputs optimal soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…With respect to the heuristic approaches for the MMR-ST, three classes of algorithms are found in the literature: (i) the two "one-scenario" heuristics HM and HU, the first proposed in [Kasperski and Zieliński, 2006] (where it is shown that it has an approximation ratio 2) and the second proposed in [Montemmani et al, 2007]; (ii) a simulated annealing (SA) proposed in [Nikulin, 2008]; and (iii) a tabu search (KMZ-TS) proposed in [Kasperski et al, 2012]. The SA approach was applied to small instances of the MMR-ST (up to 30 nodes) and reasonable results were obtained; the author pointed out that the approach should also work properly for large instances due to the search scheme used in the algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…With respect to the heuristic approaches for the MMR-ST, three classes of algorithms are found in the literature: (i) the two "one-scenario" heuristics HM and HU, the first proposed in [Kasperski and Zieliński, 2006] (where it is shown that it has an approximation ratio 2) and the second proposed in [Montemmani et al, 2007]; (ii) a simulated annealing (SA) proposed in [Nikulin, 2008]; and (iii) a tabu search (KMZ-TS) proposed in [Kasperski et al, 2012]. The SA approach was applied to small instances of the MMR-ST (up to 30 nodes) and reasonable results were obtained; the author pointed out that the approach should also work properly for large instances due to the search scheme used in the algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The SA approach was applied to small instances of the MMR-ST (up to 30 nodes) and reasonable results were obtained; the author pointed out that the approach should also work properly for large instances due to the search scheme used in the algorithm. In [Kasperski et al, 2012], the KMZ-TS algorithm was extensively tested on different sets of instances (Ya, He1, Mo and others), and it is shown that its performance is remarkably better than the one reported for the SA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations